PENGARUH TEKNIK PEMODELAN TERHADAP KETERAMPILAN MENULIS CERPEN - Handayani, Radila; Atmazaki, Atmazaki; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ This article aims to look at the effects of modeling techniques. Model problem of the ability of tenth grade students in writing short stories at the SMAN 5 Padang . Data were taken from the score without using modeling techniques and the use of modeling techniques class X SMA Negeri 5 Padang. The results showed that; First, the average value of students without the use of modeling techniques are classified as Fair ( C) 64.32. Second, the average value of using modeling techniques students classified as Good (B) 80.05. Third, the value is greater than (9.25 > 1.70), which means that the research hypothesis is accepted. Finally, it can be concluded that the use of modeling techniques, writing teaching model have a significant impact on the ability of tenth grade students in writing short stories at the SMAN 5 Padang.Â Kata kunci: pengaruh, teknik, pemodelan, menulis cerpen